Huperzine A derivative M3 protects PC12 cells against sodium nitroprusside-induced apoptosis - Ning Na; Hu Jin-feng; Yuan Yu-he; Zhang Xin-yuan; Dai Jun-gui; Chen Nai-hong (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effects of M3, a derivative of huperzine A, on the apoptosis induced by sodium nitroprusside (SNP) in PC12 cells. Methods: Cell viability was detected using MTT method. Apoptosis was examined with annexin V/prodium iodide (PI) stain. The levels of reactive oxygen species (ROS) were measured using fluorophotometric quantitation. The amount of malonaldehyde (MDA) was determined with MDA detection kits. The expression of caspase-3 and Hsp70 were analyzed using Western blotting. Results: Exposure of PC12 cells to SNP (200 μmol/L) for 24 h decreased the cell viability to 69.0% of that in the control group. Pretreatment with M3 (10 μmol/L) or huperzine A (10 μmol/L) significantly protected the cells against SNP-induced injury and apoptosis; the ratio of apoptotic bodies in PC12 cells was decreased from 27.3% to 15.0%. Pretreatment with M3 (10 μmol/L) significantly decreased ROS and MDA levels, and increased the expression of Hsp70 in the cells. Quercetin (10 μmol/L) blocked the protective effect of M3, while did not influence on that of huperzine A. Conclusion: M3 protects PC12 cells against SNP-induced apoptosis, possible due to ROS scavenging and Hsp70 induction.